Toward a synthetic hydrogen sensor in cyanobacteria: Functional production of an oxygen-tolerant regulatory hydrogenase in Synechocystis sp. PCC 6803 - Opel, Franz; Itzenhäuser, Marvin Amadeus; Wehner, Isabel; Lupacchini, Sara; Lauterbach, Lars; Lenz, Oliver; Klähn, Stephan (Frontiers in Microbiology, 2023)
Cyanobacteria have raised great interest in biotechnology, e.g., for the sustainable production of molecular hydrogen (H2) using electrons from water oxidation. However, this is hampered by various constraints. For example, H2-producing enzymes compete with primary metabolism for electrons and are usually inhibited by molecular oxygen (O2). In addition, there are a number of other constraints, some of which are unknown, requiring unbiased and systematic engineering approaches to improve the H2 yield. Here, we introduced the regulatory [NiFe]-hydrogenase (RH) of Cupriavidus necator (formerly Ralstonia eutropha) H16 into the cyanobacterial model strain Synechocystis sp. PCC 6803. In its natural host, the RH serves as a molecular H2 sensor initiating a signal cascade to express hydrogenase-related genes when no additional energy source other than H2 is available. Unlike most hydrogenases, the C. necator enzymes are O2-tolerant, allowing their efficient utilization in an oxygenic phototroph. Similar to C. necator, the RH produced in Synechocystis showed distinct H2 oxidation activity, confirming that it can be properly matured and assembled under photoautotrophic, i.e., oxygen-evolving conditions. Although the functional H2-sensing cascade has not yet been established in Synechocystis yet, we utilized the associated two-component system consisting of a histidine kinase and a response regulator to drive and modulate the expression of a superfolder gfp gene in Escherichia coli. This demonstrates that all components of the H2-dependent signal cascade can be functionally implemented in heterologous hosts. Thus, this work provides the basis for the development of an intrinsic cyanobacterial H2 biosensor that could be used to probe the effects of random mutagenesis and systematically identify promising genetic configurations to enable continuous and high-yield production of H2 via oxygenic photosynthesis.